The relationship between family background factors and scholastic achievement of children from single and two-parent families in the Mankweng Education Circuit of South Africa - Malehase, Makonde Chris (My University, 1997)
Refer to the document
Thesis (M.Ed.) -- University of the North, 1997
Keywords: Family background; Scholastic achievement; Education; Family life education -- South Africa -- Limpopo; Education -- South Africa -- Limpopo